Effect of riparian soil moisture on bacterial, fungal and plant communities and microbial decomposition rates in boreal stream-side forests - Annala, M.J.; Lehosmaa, K.; Ahonen, S.H.K.; Karttunen, K.; Markkola, A.M.; Puumala, I.; Mykrä, H. (Elsevier BV, 2022)
Riparian habitats of boreal forests are considered as hotspots for biochemical processes and biodiversity, and varying width riparian buffers have been proposed to protect species diversity of the riparian forests. However, evidence of the role of soil moisture variation in shaping riparian biodiversity and ecosystem functioning remain scarce particularly regarding belowground diversity. We studied how distance from the stream and soil moisture of the riparian zone affected species richness and community composition of plants, bacteria, and fungi as well as microbial decomposition rates. Using a split-plot design with a plant survey and amplicon sequencing for microorganisms we identified taxa associated with different categories of moisture and distance from the stream along six headwater stream-sides in middle boreal forests in Northern Finland. Tea-bag Index was used to assess the decomposition rates. PERMANOVA and linear mixed-effect models were used to analyze the data. Variation in riparian soil moisture influenced species composition and richness of plants and bacteria. Plant communities also changed from herbaceous dominated to shrub dominated with increasing distance from the stream. Fungal communities, however, did not respond to soil moisture or distance from the stream, and there were only slight differences in fungal trophic guilds among moisture and distance categories. Decomposition of organic material by microorganisms was faster adjacent to the stream than further away, and moist riparian areas had higher decomposition rates than drier ones. Decomposition rates were positively related to pH, Ca, Mg and NH4 and soil temperature. Synthesis and applications We show that above- and belowground diversity and microbial decomposition are associated to soil moisture at riparian sites supporting the idea of leaving wider unmanaged buffers in moist habitats to safeguard the overall forest diversity. Our findings further emphasize the need to consider soil moisture when planning the measures for riparian ...